Las mezclas de concreto y sus resultados en la ciudad de Tarapoto - Pinchi Vásquez, Eduardo (1997)
It is purpose of this research work to provide assessment of the effort to compression of the concrete u ti ISED 1 in di versus works of 1 city of Tarapoto, which have, as aggregates thick and aggregates from the quarry called August 10 located in the bed of the river Cumbaza fine. ,. In order to realize the objectives of the present research is fundamental need framing we in theoretical boundaries than the current REGULATIONS and STANDARDS are contributing in the development of the construction industry. in our country, and specifically to manufacture concrete refers. That has proceeded with the evaluation of the "FEATURES PHYSICAL OF THE AGGREGATES' from the quarry in reference, the same is why ~ EU shed values compatible with the technical requirements; reason why is that we set the ~ ormulacion of the respective DISEROS TEORICOS for concrete.